2013
DOI: 10.1093/aje/kws299
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Between Black and White Children in Hospitalizations Associated With Acute Respiratory Illness and Laboratory-confirmed Influenza and Respiratory Syncytial Virus in 3 US Counties--2002-2009

Abstract: Few US studies have assessed racial disparities in viral respiratory hospitalizations among children. This study enrolled black and white children under 5 years of age who were hospitalized for acute respiratory illness (ARI) in 3 US counties during October-May 2002-2009. Population-based rates of hospitalization were calculated by race for ARI and laboratory-confirmed influenza and respiratory syncytial virus (RSV), using US Census denominators. Relative rates of hospitalization between racial groups were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 16 publications
2
47
0
Order By: Relevance
“…7,19 We found that 1 underlying medical condition more than doubled the risk for severe LRTI compared with no conditions, and There are several limitations that may affect our conclusions. First, all data are from administrative records, and coding practices could affect our results.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…7,19 We found that 1 underlying medical condition more than doubled the risk for severe LRTI compared with no conditions, and There are several limitations that may affect our conclusions. First, all data are from administrative records, and coding practices could affect our results.…”
Section: Resultsmentioning
confidence: 84%
“…2 In high-income countries, 3% to 18% of pediatric admissions to the hospital are due to LRTI, 3,4 and among pediatric LRTI hospitalizations, 3% to 14% have been reported to require admission to an ICU. [5][6][7][8][9] Data on rates of pediatric hospitalizations for severe LRTI, including those requiring specialized care, such as ICU or mechanical ventilation, are limited. Such information might be useful for public health emergency planning for pandemics and other emerging respiratory infections, such as Middle East respiratory syndrome coronavirus.…”
mentioning
confidence: 99%
“…12,30 However, palivizumab's effect on our overall rates of RSV hospitalization was unlikely to be appreciable, because only a small proportion (,5%) of our study population was eligible for palivizumab, and its use was variable (30% to 70%) during most study years. 30 Day care attendance has also been described as a risk factor for RSV infection, 12 although inconsistently 7,22 ; the current work is limited by not analyzing this variable.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 For RSV infection, information is limited, but the reported severity of disease among black versus white children has been variable and inconclusive. 14,22,23 The rates of RSV hospitalization among black children ,24 months old or ,6 months old were not significantly different from those for white children. However, after 6 months of age, black children were hospitalized nearly twice as often.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation